Genetic and non-genetic factors affecting monthly test day milk yields in Karan Fries cattle - KOKATE, L S; SINGH, AVTAR; BANU, RASHIA; GANDHI, R S; CHAKRAVARTY, A K; GUPTA, A K; SACHDEVA, G K (The Indian Journal of Animal Sciences, 2013)
The present investigation was carried out using data of first lactation monthly (MTDY) test day milk yields and 305day milk yield records of 1345 Karan Fries cows sired by 84 bulls from 1984–2006 maintained at NDRI, Karnal. The effect of season of calving on all the monthly test day (MTDY) milk yields was highly significant.The monthly test day milk yields were highest in winter followed by summer in MTDY-1. However in MTDY-2 and MTDY-3, the highest milk yield was observed in winter followed by autumn, from MTDY-4 to MTDY-6; MTDY-7 to MTDY-8 and MTDY9 to MTDY-11 the highest milk yield was observed in autumn, rainy season and summer respectively. No definite trend for other seasons was observed in this trait. The effect of periods of calving on all the monthly test day yields was highly significant.The effect of period of calving on monthly test day milk yields showed no definite trend till IV period. However, the monthly test day milk yields exhibited an increasing trend from V period onwards till VIII period for MTDY-4 to MTDY-11. The effect of age at first calving on MTDY-2 and MTDY-3 was significant and on remaining monthly test day milk yields, it was nonsignificant. The h2 estimate of monthly test day milk yield was lowest for MTDY-1 and the highest for MTDY-6. The phenotypic correlations among monthly test day milk yields and with 305day milk yield were highly significant. The estimates of phenotypic and genetic correlations among all the monthly test day milk yields ranged from 0.17 to 0.82 and from 0.46 to 0.99 respectively. The magnitude of phenotypic correlations among monthly test-day milk yields decreased with increasing time interval between test day milk yields. The estimates of phenotypic and genetic correlation of monthly test day yields with 305-day milk yield ranged from 0.42 to 0.78 and 0.80 to 0.99, respectively, and the estimates was generally higher in the middle segment of lactation.